2011
DOI: 10.1039/c1ib00018g
|View full text |Cite
|
Sign up to set email alerts
|

CSF levels of oligomeric alpha-synuclein and beta-amyloid as biomarkers for neurodegenerative disease

Abstract: Protein misfolding and aggregation is a critically important feature in many devastating neurodegenerative diseases, therefore characterization of the CSF concentration profiles of selected key forms and morphologies of proteins involved in these diseases, including β-amyloid (Aβ) and α-synuclein (a-syn), can be an effective diagnostic assay for these diseases. CSF levels of tau and Aβ have been shown to have great promise as biomarkers for Alzheimer’s disease. However since the onset and progression of many n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 69 publications
3
44
0
Order By: Relevance
“…Confirming several studies showing relatively low CSF AS concentrations in both PD and DLB [731,[773][774][775], more recent ones reported significantly lower AS levels in PD [776,777] as well as in PD, DLB and MSA than in AD [777][778][779]. While CSF levels of AS oligomers were significantly increased in PD patients against controls [298,416,780], AD and progressive supranuclear palsy (PSP) [781], others were unanble to detect oligomeric AS in CSF [776]. Recent work detected alterations in AS phosphorylation (Ser129) in the CSF of PD patients [782].…”
Section: α-Synuclein As a Biomarker For Synucleinopathiessupporting
confidence: 60%
“…Confirming several studies showing relatively low CSF AS concentrations in both PD and DLB [731,[773][774][775], more recent ones reported significantly lower AS levels in PD [776,777] as well as in PD, DLB and MSA than in AD [777][778][779]. While CSF levels of AS oligomers were significantly increased in PD patients against controls [298,416,780], AD and progressive supranuclear palsy (PSP) [781], others were unanble to detect oligomeric AS in CSF [776]. Recent work detected alterations in AS phosphorylation (Ser129) in the CSF of PD patients [782].…”
Section: α-Synuclein As a Biomarker For Synucleinopathiessupporting
confidence: 60%
“…A combination of α-synuclein with other documented biomarkers may improve the discrimination between PD patients and controls. This has been reported with the combination of α-synuclein and α-synuclein oligomers levels in CSF [31][32][33]. Additional detailed studies of the levels of post-translational modified forms of α-synuclein (phosphorylated, glycosylated, nitrated, ubiquitinated or truncated forms) in biological fluids should also be explored as potential biomarkers for PD.…”
Section: Discussionmentioning
confidence: 90%
“…In one study, this ratio demonstrated 89.3% sensitivity and 90.6% specificity for the diagnosis of PD (Tokuda et al, 2010). Two additional studies have supported the application of a oligomer:total SNCA ratio ; Sierks et al, 2011). The relationship between SNCA levels and the stage of disease and/or its evolution over time is unknown.…”
Section: Alpha Synucleinmentioning
confidence: 99%